Evaluation of barley to replace milk by-product in weaning pig’s diet - Jin, Kyung Young; Hong, Jin Su; Sin, Dong Wook; Kang, Hyo Kon; Jo, Yun Young; Lee, Geon Il; Jin, Xing Hao; Jang, Jae Cheol; Jeong, Jae Hark; Kim, Yoo Yong (Journal of animal science and technology, 2019)
The supplementation level of barley was limited because of high contents of fiber in monogastric animals. Barley contained high soluble fiber, thus it could prevent to diarrhea of weaning pigs. Moreover, as the barley break down by enzymes, free sugars come out from the barley, which could be used as an energy source in weaning pigs and replace milk by-products in weaning pig's diet. Therefore, present study was conducted to investigate the influence of barley to replace milk by-product in weaning pig's diet on growth performance, blood profile, nutrient digestibility, diarrhea incidence, and economic analysis in weaning pigs. A total of 112 crossbred ([York-shire × Landrace] × Duroc, weaned at 28 days of age) piglets were allotted to 4 treatments in a randomized complete block (RCB) design. Each treatment has 7 replications with 4 pigs per pen. Pigs were fed each treatment diet which containing different levels of barley (0%, 10%, 20%, and 30%) at the expense of whey powder and lactose. Three phase feeding programs were used for 6 weeks of growth trial (phase 1: 0-2 weeks; phase 2: 3-4 weeks; phase 3: 5-6 weeks). During 0-2 week, body weight (BW), average daily gain (ADG) and G:F ratio were decreased as barley level increased in the diet (linear response, < 0.01). In blood profile, blood urea nitrogen was decreased as the barley level increased in the diet (linear, < 0.01). However, no significant differences were observed in blood glucose level. In nutrient digestibility, crude fat digestibility was linearly increased as barley increased (linear, < 0.01). The incidence of diarrhea was improved as increasing barley contents in all phases (linear, < 0.01). These results demonstrated that supplementation of barley to replace milk by-product influenced negatively on growth performance during 0-2 week. However, the incidence of diarrhea and later growth performance from 3 week postweaning were improved as dietary barley level increased.